Jenis-Jenis dan Prevalensi Ektoparasit Pada Anjing Peliharaan - Kiki Martha Puri; - Dahelmi; - Mairawita (Universitas Andalas, 2014)
Dogs are the most popular pet animal although they could carry ectoparasites which can cause diseases in human. The purposes of this study were to identify ectoparasites and to determine their prevalence on pet dogs. This study was conducted from March to July 2013 using survey method and collecting ectoparasites directly from 15 pet dogs in Padang. Specimen processing and species identification were done at the Animal Taxonomy Laboratory, Biology Department, Andalas University. This study found 5 species of ectoparasites in pet dogs. There were Ctenocephalides canis Curtis, 1826, Dermacentor sp., Haemaphysalis sp., Rhipicephalus sanguineus Latreille, 1806 and one unidentified species sp. 1 from family Laelapidae. Rhipicephalus sanguineus has the highest prevalence (73,3 %) followed by Haemaphysalis sp. (46,7%), Dermacentor sp.(20%), Ctenocephalides canis (13,3%) and sp. 1 from Family Laelapidae (6,7%).Keywords : ectoparasite species, prevalence, pet dogs